Saúde e saneamento: doenças causadas por veiculação hídrica nas áreas Riacho Doce Pantanal em Belém/PA e desafios da intersetorialidade - MANCABÚ, Milanca (Universidade Federal do Pará, 2015)
This work aims to study the relationship between the incidence of diseases caused by hydric transmission and sanitation in existing areas of Riacho Doce and Pantanal, located around the Hydrographic Basin Tucunduba in Belém / PA. Its goal is to analyze the relationship between the incidence of these diseases and health conditions existing in the selected areas and discuss the intersectionality between public health policies and sanitation. His methodological approach, based on critical social theory encompassed literature, documentary research and field research. Literature search were discussed determinants of inequalities in the process of urban space occupation and the consequent social segregation revealed by degradation of living conditions in regard to the denial of access to essential public services. In documentary research surveys were made along the federal entities, state and municipal governments to identify regulatory frameworks (plans, laws, resolutions and regulations) regarding the policies of health and sanitation. Among these agencies highlights the City Department of Health (SESMA), the Department of Health (SESPA), the Ministry of Health (MOH) and the System Diseases Information and Notification (SINAN). In field research, of qualitative nature were conducted eleven (11) semistructured interviews, seven (7) with residents and four (4) with technicians working in the areas of Riacho Doce and Pantanal. The results show that in the mentioned areas, marked by poor sanitation conditions, addressing risk factors to the spread of diseases caused by hydric transmission can only be realized through the use of intersectorality tool in the process of management of public health policies and sanitation.